Implementasi Teknologi Karbon Aktif Berbahan Arang Batok Kelapa untuk Pengolahan Air di Kawasan Pertambangan Desa Supat Barat Sumatera Selatan - Lina Rianti; Maryana Maryana; Euis Kusniawati (BADAN PENERBIT STIEPARI PRESS, 2026)
The availability of clean water has become a major problem for the community of Supat Barat Village, Babat Supat District, Musi Banyuasin Regency, South Sumatra Province. The well water used in daily life is still acidic (low pH) and turbid. This is influenced by geological factors as well as mining activities around the village area. This community service activity aims to process water so that it can produce clean water that can be used by the local community. The solution applied is based on simple technology by utilizing active carbon from coconut shell charcoal as a water filter medium. The activities are carried out through eight visits covering socialization, counseling, training, technology implementation, assistance, evaluation and program sustainability planning. The result of the activities showed an increase in community knowledge by up to 83%, the production of active carbon totaling 10 kg, as well as the installation of four units tha functioned well with a capacity if 5000 liters per day. This program has proven effective in improving water quality and strengthening the socio-economic capacity of the community, while also contributing to the achievement of university performance indicators, the SDGs targets on clean water and sanitation, and efforts towards water self-sufficiency at the village level.